Antifungal activity of a novel synthetic polymer M451 against phytopathogens - Tetz, Victor; Kardava, Kristina; Krasnov, Konstantin; Vecherkovskaya, Maria; Tetz, George (Frontiers in Microbiology, 2023)
Phytopathogenic fungi are the predominant causal agents of plant diseases. Available fungicides have substantial disadvantages, such as being insufficiently effective owing to intrinsic tolerance and the spread of antifungal resistance accumulating in plant tissues, posing a global threat to public health. Therefore, finding a new broad-spectrum fungicide is a challenge to protect plants. We studied the potency of a novel antimicrobial agent, M451, a 1,6-diaminohexane derivative, against different phytopathogenic fungi of the Ascomycota, Oomycota, and Basidiomycota phyla. M451 exhibited significant antifungal activity with EC50 values from 34–145 µg/mL. The minimal fungicidal concentration against Fusarium oxysporum ranged from 4 to 512 µg/mL depending on the exposure times of 5 min to 24 h. M451 has the highest activity and significantly lower exposure times compared to different polyene, azole, and phenylpyrrole antifungals. The conidial germination assay revealed that M451 induced 99% and 97.8% inhibition against F. oxysporum within 5 min of exposure to 5000 and 500 µg/mL, respectively. Germ tube elongation, spore production, and spore germination were also significantly inhibited by M451 at concentrations of ≥50 µg/mL. Based on the broad spectrum of antifungal effects across different plant pathogens, M451 could be a new chemical fungicide for plant disease management.